2014
DOI: 10.5007/2175-7925.2014v27n2p157
|View full text |Cite
|
Sign up to set email alerts
|

Origem e distribuição do plexo lombossacral da paca (Cuniculus paca, Linnaeus 1766)

Abstract: ResumoConsiderando a importância da paca como fonte proteica alternativa à população e, em especial, por apresentar características adequadas à pesquisa como modelo experimental, objetiva-se descrever a origem e a distribuição do plexo lombossacral da paca, visando colaborar com o melhor conhecimento de sua morfologia, cuja descrição é escassa na literatura. Foram utilizadas oito pacas adultas (Cuniculus paca) de ambos os sexos, provenientes do criatório do Setor de Animais Silvestres da Faculdade de Ciências … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 5 publications
2
14
3
7
Order By: Relevance
“…This formation resembles that of the porcupine (T15, L1-L3) (Aydin), and differs from that observed in rabbits of this study. Oliveira et al (2008) observed that in the cavy (Galea spixii), the femoral nerve originated from the ventral roots of L5 and L6, similar to that observed by Tonini et al (2014) in the paca (Cuniculus paca) and partly similar to the results found in the present investigation. Martinez-Pereira & Rickes (2011) observed that in the chinchilla (Chinchilla lanigera), the femoral nerve originated from the ventral roots of L4 and L5, in part similar to the results found in the present investigation (only in males).…”
Section: Discussionsupporting
confidence: 81%
“…This formation resembles that of the porcupine (T15, L1-L3) (Aydin), and differs from that observed in rabbits of this study. Oliveira et al (2008) observed that in the cavy (Galea spixii), the femoral nerve originated from the ventral roots of L5 and L6, similar to that observed by Tonini et al (2014) in the paca (Cuniculus paca) and partly similar to the results found in the present investigation. Martinez-Pereira & Rickes (2011) observed that in the chinchilla (Chinchilla lanigera), the femoral nerve originated from the ventral roots of L4 and L5, in part similar to the results found in the present investigation (only in males).…”
Section: Discussionsupporting
confidence: 81%
“…However, results differed from those in the chinchilla (MARTINEZ-PEREIRA; RICKES, 2011) derived exclusively from L 3 , and in the paca (TONINI et al, 2014) derived exclusively by L 4 .…”
Section: Discussioncontrasting
confidence: 44%
“…The nerve in the red squirrel (AYDIN, 2010) derived from L 3 and demonstrated a nerve arrangement different from that of the gerbil. The cutaneus femoris lateralis nerve has a similar formation as that of the anteater (CRUZ et al, 2014), differing from reports on the chinchilla (MARTINEZ-PEREIRA; RICKES, 2011) formed exclusively from L 4 , and on the paca (TONINI et al, 2014) derived from L 5 .…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations